Blockchain Technology and Accounting: Revolutionizing Transparency, Trust, and Efficiency in Financial Reporting - Armiani, Armiani; Sardju, Himawan; Nursansiwi, Dwi Arini; Jairin , Jairin (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate the impact of implementing blockchain technology in accounting practices on transparency, trust and efficiency in financial reporting. Using the systematic literature review method, relevant articles from reputable international databases, such as Scopus, have been collected and analyzed. The analysis results show that blockchain technology has brought a significant change in the transparency paradigm, by providing distributed and non-manipulable transaction records, as well as strengthening trust by providing open and transparent access to financial information. Apart from that, the use of blockchain technology has also had a positive impact on efficiency in the financial reporting process through automation and reduced administrative costs. The implication of these findings is that it is important for accounting organizations and practitioners to consider adopting blockchain technology as part of their strategy to improve the quality of financial reporting and strengthen public trust. Future research could further explore the potential and challenges of blockchain technology in accounting practices as well as steps that can be taken to optimize it in organizational operations.